Diagnóstico y perspectivas del periodismo como profesión y su servicio a la comunidad - JIMENEZ, JORGE MANUEL (2015)
This research is a study that aims to perform a "DIAGNOSIS AND PROSPECTS journalism as a profession and service to the community." The concern of media professionals and graduates in this field is the question of the possibility that the values defined in the professional world today, do not fit in the new guidelines of the communication law. Since in the different media in the province of Loja news general information is disseminated, and there is a space for discussion and opinion regarding the content of this bill it is considered of social interest. The overall objective was to make a diagnosis and determine the prospects of journalism as a profession and community service in the city of Loja. To meet the objective was necessary to base the methods, hypothetical-deductive based on experience and general knowledge will allow to meet the objectives and methods that have been proposed, inductive-deductive the same as from general data accepted as valid to reach a conclusion of a particular type and vice versa, and for mathematical and statistical analysis and interpretation of the survey. Techniques such as the survey determined, preferences etc., by the lojana community. And the interview that yielded the information from managers of the media. The analysis and synthesis in order to join parts of the project that will enable a minimum degree of decoding error in all of it. From the results it was determined that the Social Communication professionals, 52% have a regular job; 39% of respondents said that their first job he did on some means of social communication, however 66% of 388 respondents said that locally provided services. With regard to the knowledge acquired in university classrooms, 77% of respondents say that if you served them for their professional life, and 66% said that work on what you want, or in some media and also indicate your prospects as journalists in the community are excellent (46%). In regard to local labor supply 43% believe that if there are areas where labor. A management level, show that if there are good professionals in the area of social communication, but also require a lot of ongoing training and upgrading the use of current information technology.